A green approach for the decoration of Pd nanoparticles on graphene nanosheets: An in situ process for the reduction of C–C double bonds and a reusable catalyst for the Suzuki cross-coupling reaction1. (27th August 2015) - Hussain, Najrul; Borah, Ashwini; Darabdhara, Gitashree; Gogoi, Pranjal; Azhagan, Vedi Kuyil; Shelke, Manjusha V.; Das, Manash R.
<x xml:space="preserve">Abstract</x> In situ synthesis of Pd nanoparticles on graphene nanosheets with simultaneous reduction of alkene to alkane using hydrogen gas were utilized as efficient catalysts for the Suzuki cross-coupling reaction.